Two draft building specifications from 1538 for the construction of a roof on a monastery church in IJsselstein (Bulletin KNOB, 2020)
Until 1577 there was a monastery of the Cistercian order in IJsselstein. It had been founded by the local lords in 1342. Subsequently, the buildings were destroyed several times by acts of war. In 1495 a new complex was founded within the town walls in Benschopperstraat. Part of this survived and was restored in 1984. During the building of the church, part of the complex was burnt down, among which the monastery church. After fund-raising the reconstruction could start in 1539.Within this scope specifications were made for the construction of a roof on the church. Preparatory to this, exploratory visits were paid to other monasteries. Of this campaign two building specifications have been preserved, one of them dated 1538. These two specifications are of importance for the building history because of some differences in the defined construction principles in the two specifications. An important difference indicates that at that time the transition took place from the spanned roof to the roof with a needle in the ridge of the roof.